Haemostasis and oral hormone replacement therapy - Stachowiak, Grzegorz; Połać, Ireneusz; Stefańczyk, Ludomir; Jędrzejczyk, Sławomir; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2002)
Objective: The aim of the study was to evaluate some haemostatic changes in women taking oral hormone replacement therapy (HRT). Materials and methods: In 33 women aged 45–64 years with osteoporosis and climacteric symptoms several fibrinolytic and coagulative parameters were measured. These measurments, together with sonographic examinations of venous system of pelvis and low extremities, were performed three times in each women – before and after three and six months of HRT. Hormonal therapy consisted of oral estradiol valerate and levonorgestrel. Results: Activity of factor VII was decreased significantly during the trial. No other significant modifications in the examined parameters were detected. No signs of venous thromboembolism were found in sonographic examinations. Conclusions: The hormone replacement therapy can reduce the risk of coronary heart disease thanks to decreased levels of factor VII. We did not observed any procoagulative changes and increased risk of venous thromboembolism during this kind of treatment.